Penyerapan Air Glass Fiber Non Dental – Fiber Reinforced Composite dalam Larutan Mouthwash - Etny Dyah Harniati; Widjijono Widjijono; Budiono Budiono (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2021)
Fiber reinforced composite (FRC) is widely used to replace porcelain fused to metal (PFM) for patients who have lost teeth. Fiber reinforced composite is resin matrix protheses with fiber reinforced to get optimal strength. Glass fiber dental is often used because it does not require complex preparations, not sensitive to chemicals and moisture, but it has an expensive price for Indonesian people and limited availability. An alternative material such as glass fiber non dental can used. Mouthwash is used as an antiseptic and anti-plaque material on the oral cavity. Mouthwah can affect of water sorption of FRC. The aim of this study is to know effect of mouthwash on the absorption of water in non dental glass fiber - reinforced FRC. Sixty specimens divided into four groups (n=4), 2 groups with glass fiber dental soaked on the bisguanida and aquades, 2 groups with glass fiber non dental soaked on the bisguanida and quaternary ammonium. The data analyzed with Anova. Anova test showed that there is an influence of mouthwash bisguanide and quartenary ammonium compounds on the value of absorption of glass fiber reinforced composite water (p<0,05). Water sorption of FRC in bisguanide mouthwash is higher than quartenary ammonium compounds.